Hubungan Asupan Makronutrien, Aktivitas Fisik, dan Status Gizi dengan Usia Menarche Pada Remaja Perempuan Usia 9-15 Tahun di Desa Kedunglosari Kabupaten Jombang - Tri Sutanti Puji Hartati; Farapti Farapti; Emyr Reisha Isaura (Universitas Airlangga, 2022)
Background: Menarche is the first menstruation experienced by adolescent girls. The age of menarche in Indonesia has decreased from 13 years in 2010 to 12.4 years in 2018. The age of menarche is influenced by internal and external factors, some of the factors are macronutrient intake, physical activity, and nutritional status. The decrease in age at menarche is associated with an increased likelihood of uterine myoma, dysmenorrhea, and breast cancer. Objectives: To analyze the relationship between macronutrient intake, physical activity, nutritional status and age at menarche in adolescents Girl 9-15 years old. Methods: This research used cross sectional design with sample size of 87 adolescent girls who had experienced menstruation and selected using simple random sampling. Data were collected by macronutrient intake used Semi-Food Frequency Questionnaire (SQFFQ), physical activity used Short Form International Physical Activity Questionnaire (SF-IPAQ), anthropometric data to assess nutritional status through measurement of body weight and height and age of menarche used a self-report questionnaire. Data was analyzed by t-test, chi-square and linear regression with 95% confidence level. Result: There was a significant relationship between fat intake (p = 0,049) and nutritional status (β = -0.92, p <0.001) with the age of menarche. The results of the analysis showed that there was no significant relationship between energy intake (p = 0,058), protein intake (p = 0,178), carbohydrate intake (p = 0,099), and physical activity (p = 0,422) with age at menarche. Conclusions: fat intake and nutritional status during adolescence is related to the age of menarche. Prevention for cancer in women should be carried out as early as possible when adolescent girls have not menarche. One of prevention is managing the nutritional status of adolescent girls by paying attention to diet. Keywords: nutritional status, macronutrient intake, physical activity, age at menarche, adolescent girls